Transformasi atau Distorsi? Tinjauan Literatur tentang Dampak Generative Artificial Intelligence terhadap Pemikiran Kritis Mahasiswa Akuntansi - Arifa Kurniawan (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
The emergence of Generative Artificial Intelligence (Gen AI), such as Chat GPT, has significantly influenced higher education, raising the question of whether this technology strengthens or disrupts the learning process. This study examines the impact of the use of Generative Artificial Intelligence (GenAI) on the critical thinking of accounting students through a review of the literature of various indexed scientific journal articles, taking into account its transformative opportunities and risks.. The findings indicate that Gen AI has the potential to be an enriching tool through the personalization of materials, enrichment of learning resources, teaching efficiency, and rapid feedback. In accounting studies, Gen AI can also assist students in analyzing more complex cases. However, unguided use can lead to distortions, such as weakened independent thinking, superficial understanding, a decline in the authenticity of academic work, and the emergence of an unwarranted sense of competence. This study confirms that the impact of Gen AI is largely determined by the user's digital literacy, purpose of use, curriculum design, teaching methods, and the ethical policies implemented by the institution. Therefore, a collaborative effort among institutions, lecturers, and students is necessary to strengthen AI literacy, integrate it appropriately into learning, and ensure clear ethical guidelines so that Gen AI genuinely supports the development of critical thinking skills in accounting students.